Monitoring Of Preservative Detection Devices In Market Foodstuffs - Anugrah pratama; Nina paramitha; Tamsir Ariyadi; Endah Fitriani (Program Studi Teknik Elektro Universitas Khairun, 2026)
Food safety is a crucial issue in Indonesia, especially regarding the use of hazardous preservatives such as formaldehyde in street food. Manual monitoring of formaldehyde use is often ineffective, so an automated system is needed to detect formaldehyde in real time. This study aims to develop an Internet of Things (IoT)-based formaldehyde detection system using an ESP32 microcontroller equipped with an ultrasonic sensor for automatic object detection. The detection data is sent to a Telegram-based platform. The test results show that this system is capable of accurately detecting objects at a distance of 0-20 cm and measuring voltage well to ensure the stability of the device. Testing of food samples shows the presence of borax in some street food, which proves the effectiveness of the system in detecting harmful preservatives and improving food safety.